Optimization of Phlorizin Extraction from Annurca Apple Tree Leaves Using Response Surface Methodology - Maria Maisto; Vincenzo Piccolo; Ettore Novellino; Elisabetta Schiano; Fortuna Iannuzzo; Roberto Ciampaglia; Vincenzo Summa; Gian Carlo Tenore (MDPI AG, 2022)
Phlorizin is a plant-derived molecule with relevant anti-diabetic activity, making this compound a potential functional component in nutraceutical formulations for the management of glycemia. It is noteworthy that promising sources for the extraction of phlorizin include apple tree leaves, a by-product of apple fruit production. The main aim of this study was to optimize the extraction process of phlorizin from Annurca apple tree leaves (AALs) using response surface methodology (RSM), and to determine the potential nutraceutical application of the obtained extract. The results of the RSM analysis indicate a maximum phlorizin yield of 126.89 ± 7.579 (mg/g DW) obtained under the following optimized conditions: MeOH/H2O, 80:20 + 1% HCOOH as the extraction solvent; 37.7 °C as the extraction temperature; and 170 min as the time of extraction. The HPLC-DAD-HESI-MS/MS analysis performed on the extract obtained under such conditions, named optimized Annurca apple leaves extract (OAALE), led to the identification of twenty-three phenolic molecules, with fifteen of them quantified. To explore the nutraceutical potential of OAALE, the in vitro antioxidant activity was evaluated by DPPH, ABTS, and FRAP assays, resulting in 21.17 ± 2.30, 38.85 ± 0.69, and 34.14 ± 3.8 μmol Trolox equivalent/g of extract, respectively. Moreover, the IC50 of 0.330 mg/mL obtained from the advanced glycation end-product inhibition assay, further supported the antidiabetic potential of OAALE.